RARE EPHEMERA FROM BOTH SIDES: A DIGITAL COLLECTIONS AND CURATION CASE STUDY OF RUSSIA (THE SOVIET UNION) AND ASIA [PRESENTATION] - Spencer, George Andrew (Nazarbayev University Library, 2021)
This presentation is a Digital Collections and Curation case study involving several very rare items that the University of Wisconsin-Madison Department of Special Collections has recently acquired which are in the process of being converted into Open Access digital collections to enhance access for scholars worldwide. The unifying theme of these materials is rare ephemera representing various stages of Russian-Asian relations. This presentation focuses on the process of acquiring these very rare items, the partnership between subject specialist Bibliographers and Special Collections Librarians in curating these collections, collaboration with faculty in determining the potential research value and use cases for the materials, the physical and digital processing of such rare and fragile materials, the research involved in determining the historical context of the items, metadata creation in multiple languages, digital infrastructure, preservation of the physical originals, etc. One of these collections consists of over 60 original Russian propaganda news placards from the Russo-Japanese War era as well a set of propagandistic chromolithographs of battle scenes of the Russo-Japanese War. In addition, we have recently acquired an original Russian colored print in the lubok (лубок) style also from the Russo-Japanese War period. A second collection is a very rare complete run of an illustrated Ottoman Turkish magazine about the Russo-Japanese War. This magazine demonstrates the great interest among the Turkish people of the time in the Russo-Japanese War and its outcome. A third collection comprises a scrapbook of photographs documenting an anti-Soviet exhibition held in Japan circa 1940. As far as we have been able to determine, it is the sole remaining historical record of an exhibition called "赤色ロシヤを発く展覧会" (Akairo roshiya o abaku tenrankai = Debunking of Red Russia). This exhibition gives a unique insight into the state of Japanese-Soviet relations as reflected in Japanese popular culture in the period immediately before World War II. A fourth item acquired and made available Open Access by UW-Madison Libraries’ Digital Collections Center is a digital surrogate of an 18th century Kazakh dictionary lexicon for which the original unique manuscript is held by the Department of Manuscripts and Rare Books (Отдел рукописей и редких книг) of the Russian National Library in St. Petersburg, Russia. This dictionary lexicon was compiled during the period of gradual expansion of Russian influence in the northeastern Kazakh steppe in the late 18th Century.
Keywords: Type of access: Open Access; EALC